PEMBERDAYAAN UMKM MELALUI PENGUATAN KOPERASI SYARIAH SEBAGAI UPAYA MENINGKATKAN EKONOMI MASYARAKAT DESA MANDALASARI - Anggi Fitrianingsih; Ardian Hanapi; Herani Oktavia; Maula Azkia L.A.R; Zahra Naila P; Dadin Solihin; Maryati; Nina Ismiyanti; Nida Hidayatul Ummah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) – Sekolah Tinggi Agama Islam (STAI) Pelita Nusa Bandung Barat, 2025)
Community economic empowerment based on Islamic values is an essential strategy for enhancing independence and improving the welfare of rural communities. This Community Service Program (CSP/PkM) was implemented in Mandalasari Village, Cikalong Wetan District, West Bandung Regency, an agrarian village with strong economic potential but limited business management capacity, access to capital, and institutional support. The program aims to strengthen the capacity of Micro, Small, and Medium Enterprises (MSMEs) through the development of a sharia-based cooperative as a collective economic institution. Using the Participatory Action Research (PAR) approach, community members were actively involved in problem identification, sharia cooperative socialization, business management training, financial literacy activities, and the facilitation of the establishment of the “Koperasi Merah Putih Syariah.” The results show significant improvements in the community’s understanding of Islamic economic principles, basic financial record-keeping skills, and collective commitment to building a sharia-based cooperative. Beyond economic benefits, the program also strengthened social values such as honesty, trustworthiness, and cooperation. This Community Service Program demonstrates that strengthening sharia cooperatives is an effective method for fostering equitable and sustainable socio-economic transformation in rural communities and can be replicated in other regions by adapting to local potentials.